(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we introduce and study the concept of nearly boundedness on arbitrary subsets in topological spaces which depended on the notion of regular closed remoted neighborhood system. Several characterizations of nearly boundedness in terms of convergence theory of filter, molecular nets and ideals are obtained. We prove that the concept is good extension, productive and topologically invariant.